Lost. The complete fourth season. The expanded experience [videorecording (DVD)] - Fox, Matthew, 1966-; Lilly, Evangeline, 1979-; Monaghan, Dominic, 1976-; Garcia, Jorge, 1973-; Grace, Maggie, 1983- (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2008)
More than three months after their fateful crash, the survivors of Oceanic Flight 815 will discover that the only thing more dangerous than the island might be the people who have come to rescue them.